ANALISIS KOORDINASI KELEMBAGAAN DALAM PENYELENGGARAAN PENYULUHAN PERTANIAN (Studi Kasus Kec. Berastagi Kab. Karo) - Nana Nurlina Ginting; Matius Bangun (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2021)
The extension of the extension is strongly influenced by the extension institution itself both structurally from the center to the regions and functionally in the regions in relation to other cross-sectoral relations. The dynamics of changes in extension institutions from the central government have influenced institutional changes in the regions, both in terms of materials, methods and funding of extension. This research uses the descriptive qualitative method with the main problem is how to coordinate the implementation of agricultural extension in a Strutural and Functional manner and what efforts are made by the Karo Regency Government in responding to the dynamics of change so that it can still improve the performance of agricultural extension workers. The conclusion of this study is that in order to anticipate the dynamics of institutional changes, extension coordination is placed in the Functional (non-structural / non-structural / non-esslon) Agricultural Extension Coordination Secretariat which is accountable to the District Head through the Head of the Agricultural Service. Efforts that can be made by local governments in accordance with farmers' perceptions in terms of extension methods are: a. PPL visits to locations, b. Open Group Discussion, c. Demonstration Plots and d. Socialization.In terms of extension material are: a. Marketing Network, b. Latest drug, fertilizer and pesticide information, c. Nursery and Cultivation Techniques, and d. Post Harvest Handling; while striving for financing comes from: a. APBN, b. Provincial APBD, c. Karo Regency APBD and and d. Non-binding Third Party.